Helicobacter pullorum Outbreak in C57BL/6NTac and C3H/HeNTac Barrier-Maintained Mice - Boutin, S. R. (American Society for Microbiology (ASM), 2010)
Helicobacter pullorum is a bacterial pathogen in humans. By using microaerobic culture techniques, H. pullorum was isolated from the feces of barrier-maintained mice and identified, on the basis of biochemical, restriction fragment length polymorphism, and 16S rRNA gene sequence analyses. This finding presents an opportunity to study H. pullorum pathogenesis in mice.